The Effect of Islamic Financial Literacy on The Interest in Saving at Islamic Banks - Nur Aziza; Amel Deswanda (Prosperia: Journal of Economic Development, Accounting, and Global Markets, 2026)
This study examines the empirical effect of Islamic financial literacy on the public interest in saving at Islamic banks within a dual financial system. Utilizing an explanatory quantitative approach and a cross sectional survey design, primary data were gathered through highly structured closed ended questionnaires distributed via purposive sampling to the retail banking consumer market in Indonesia. The primary data underwent classical econometric diagnostics and simple linear regression parameter evaluation. The statistical results reveal that Islamic financial literacy exerts a significant positive influence on saving interest, confirming that cognitive determinants act as structural drivers of behavioral intentions. The empirical model explains more than one third of the total variance in consumer saving interest, validating the fundamental tenets of the Theory of Planned Behavior. These findings address historical research gaps and provide strategic insights for resolving national market anomalies, such as the gap between high sharia literacy levels and low operational inclusion indices. Regulatory bodies and Islamic commercial banking institutions should prioritize structured educational frameworks and digital marketing outreach to optimize asset growth and secure a broader national market share.